616 Preventing Biofilms on BACTIGON® Coated Camstent Urinary Catheters in Patients Undergoing Elective Colorectal Surgery: A Single Centre Pilot Study. (4th May 2021) - Lewis-Lloyd, C; Dubern, J; Kalenderski, K; Halliday, N; Alexander, M; Irvine, D; Adiamah, A; Williams, P; Hume, D
Abstract: Introduction: Catheter associated urinary tract infections account for 40% of hospital acquired infections. They are associated with biofilms consisting of bacterial cells enmeshed in a self-generated extracellular matrix adhering to catheter surfaces. We have developed a novel polymer family that, coated onto urinary catheters, creates a "non-stick" surface preventing biofilm development. Method: Prospective cohort of elective colorectal patients recruited pre-operatively, received a standard silicone (SS) or Camstent (BACTIGON®) coated urinary catheter. After removal, catheters were cut longitudinally into 3 segments. Biomass and biomineralisation were analysed using confocal fluorescence microscopy. Data were normalised by square rooting the catheter indwelling duration. Environmental scanning electron microscopy and energy dispersive x-ray spectroscopy was performed. Results: Of 40 patients, 20 each received a SS or coated catheter. Between SS and coated catheters, average indwelling duration was similar and biofilm biomass was 32.068µg/cm 2 (95%CI ±21.950) vs. 1.948µg/cm 2 (95%CI ±2.595) (P = 0.0111). Confocal microscopy suggested a 93.93% reduction in biofilm biomass on coated catheters. Mineral compositions were different with biofilm and struvite/apatite on SS and calcium oxalate, endogenously derived, on coated catheters. Conclusions: Inert BACTIGON® coated catheters appear superior at preventing biofilm formation than SS catheters. Clinical trials are needed to determine the clinical and health economic benefit of this intervention.